2016
DOI: 10.1017/s1751731116000392
|View full text |Cite
|
Sign up to set email alerts
|

Use of dietary rosemary diterpenes to inhibit rancid volatiles in lamb meat packed under protective atmosphere

Abstract: The objective of the present study was to determine the inhibitory effect of dietary rosemary diterpenes on the formation of the volatile organic compounds (VOCs) responsible for rancid flavour in raw lamb meat. The lamb diet was supplemented during the fattening stage with two levels (200 and 400 mg/kg feed) of a dietary rosemary extract (DRE) containing carnosic acid and carnosol (1 : 1, w/w). The formation of VOCs (determined by headspace solid-phase microextraction at 40°C and MS) and odour deterioration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…A high level of PUFA was found in the intramuscular fat of deer meats, and autoxidation could be initiated more readily in this type of meat [42]. Some authors observed aldehydes inhibition in different meat products using natural antioxidants [43,44]. In our case, the total quantity of aldehydes increased in control samples during chilled storage in MAP; however, in the burgers with lees, it remained constant (except in the case of the Lpb sample).…”
Section: Volatile Compoundsmentioning
confidence: 38%
“…A high level of PUFA was found in the intramuscular fat of deer meats, and autoxidation could be initiated more readily in this type of meat [42]. Some authors observed aldehydes inhibition in different meat products using natural antioxidants [43,44]. In our case, the total quantity of aldehydes increased in control samples during chilled storage in MAP; however, in the burgers with lees, it remained constant (except in the case of the Lpb sample).…”
Section: Volatile Compoundsmentioning
confidence: 38%
“…Concretely, octanal was the one that was found in greater presence in the lambs reared under intensive conditions (2.30 AU × 10 4 /g fresh meat), while it did not appear in the lambs reared extensively. This fact could indicate that intensively-reared lambs may have a greater intensity of rancid odor, since previous studies have found that octanal is the aldehyde that presented the highest correlation with this parameter in lamb meat packed under a protective atmosphere [ 76 ]. On the contrary, nonanal was only detected in extensively-reared lambs since it is the aldehyde that appears in the highest concentration in the meat of these animals (2.56 AU × 10 4 /g fresh meat), after 2-propenal with a concentration of 4.04 10 4 /g fresh meat, which would provide a plastic and soapy aroma [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…These differences could be related to the possible variability of the fatty acid profile of lambs [ 88 ] because the main origin of esters is the esterification of carboxylic acids [ 89 ]. Despite the differences, previous studies have shown that the contribution of esters to the aromatic profile of lamb meat may be low [ 68 ]; several authors did not even detect these compounds [ 17 , 81 , 90 , 91 ] or detected a low number of esters [ 37 , 76 , 87 , 88 ]. Therefore, although the fraction of esters to the total volatile compounds was relatively high (3.35 in intensively-reared lambs and 3.51% for lambs reared under extensive conditions) ( Figure 1 ), their presence may not contribute to the overall aroma of the lamb meat.…”
Section: Resultsmentioning
confidence: 99%
“…It seems paradoxical that given the growing concern for food safety, the packing attribute is only fifth in the order of importance among lamb meat consumers, with similar results in both 2004 and 2014, since packing serves as a container, protecting the meat from physical and chemical deterioration [ 44 ] and environmental contamination [ 45 ], and favoring longer shelf life as a result of various strategies, such as controlling temperature and moistness, adding different products [ 46 ] and oxygen removal, or a combination of these. Packing is thus a key element in the guarantee of quality and food safety [ 47 ].…”
Section: Resultsmentioning
confidence: 99%